The Isyārī Approach in Hadith Jurisprudence among Prominent Sufi Figures: The Transformation of the Method of Esoteric Interpretation from the Qur'anic Text to the Prophetic Hadith - Khairul Bahri Nasution; Muhammad Sulton (Fakultas Ushuluddin Adab dan Dakwah UIN Sultanah Nahrasiyah Lhokseumawe, 2026)
The isyārī approach has predominantly been studied within the context of Qur’anic exegesis, while its application in understanding Hadith (fiqh al-ḥadīth) has received relatively limited attention, particularly regarding the validity of Sufi interpretations through sanad criticism, matn analysis, and measurable epistemological parameters. This study aims to analyze the application of the isyārī approach in Hadith interpretation among Sufi figures and to examine its validity based on the parameters established by al-Shāṭibī. This research employs a qualitative library research method. The data were analyzed using content analysis combined with sanad and matn criticism of Hadith, and further examined according to the two parameters of accepting isyārī interpretation proposed by al-Shāṭibī. The primary sources of this study include Sufi works such as Risālat al-Mustarsyidīn, Ḥālat Ahl al-Ḥaqīqah ma‘a Allāh, and Jawāhir al-Ma‘ānī. The findings reveal that the Hadiths employed in isyārī interpretation are generally classified as maqbūl, with ḥasan and ṣaḥīḥ quality, except for one Hadith considered weak. Symbolic interpretations are found in several terms, such as jasad and iṣba‘, while other terms remain consistent with their linguistic meanings and Islamic legal usage. This study demonstrates that the isyārī approach in Hadith interpretation can be accepted as long as it does not contradict Hadith authenticity, linguistic principles, and does not generate new legal rulings.